Distraction osteogenesis over intramedullary nail : a report of two cases - Sulaiman , Razak; Munajat, Ismail; Yaakub, Ismail; Awang, Mohd Shukrimi (Malaysian Medical Associations, 2006)
Distraction osteogenesis over intramedullary nail has a benefit of decreasing the time for external fixator thus reducing the rate of associated complications. However, risk of panosteomyelitis is still the major worry. We are reporting two patients who underwent the procedure. The first case was a 13-year-old girl requiring 6 cm of femoral lengthening and the second case was a 17-year-old girl who required 5 cm of tibial lengthening. The healing index was 19.5 days/cm and 14.8 days/cm respectively, compared favorably to 30 days/cm with traditional method of distraction osteogenesis. There were mild pin tract infections and joint stiffness which responded to non-operative treatment.